Pendampingan Penetapan Identitas Desain Motif Ragam Hias Pengrajin Batik Singosari - Indrowaty, Sri Aju -; Rahmawati, Femi Eka; Perdhani, Widya Caterine; Hartono, Didik (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
The development of batik has spread to almost all subdistricts and villages, especially in East Java. Each community strives to produce and find uniqueness in creating their batik motifs. In Singosari Subdistrict, Malang Regency, there is a community of batik craftsmen from villages and subdistricts in the Singosari area, namely the Singosari Batik Association. To date, numerous batik motifs have been created. However, these have not yet met sales targets due to the lack of a distinctive and unique batik identity from the artisans of the Singosari Batik Association. Therefore, guidance is needed in exploring ideas for motifs, as well as experimenting with forms, compositions, and colors in designing batik motifs that can reflect the identity of Singosari batik artisans. In exploring the uniqueness of Singosari motifs, two approaches are used. The first is through the traditional culture of Singosari, which can be traced back to the historical greatness of the Singosari kingdom in the past. The second approach is through the culture that has been developed in the present day. These two approaches can be used to describe the form of Singosari motifs. To strengthen the identity of Singosari motifs, color can also support the composition of the motifs. When determining the characteristic colors of Singosari, natural colors can be sourced from plants that grow and are endemic to Singosari. Some motifs resulting from the redesign of craftsmen's sketches have also been re-explored and transformed into new motifs that craftsmen can use as design inspiration for future batik creations. The diversity of attractive batik motifs will undoubtedly influence consumer purchasing power, thereby increasing the production output of the Singosari Batik Association. It is hoped that the batik fabric produced will once again become the signature fabric of Singosari, recognized by all segments of society, and represent East Java both domestically and internationally in the future.